3+5(x-4)
= 3 + 5x - 20
= 5x - 17
3(x-6) = -12
3x - 18 = -12
3x = 6
x = 2
So, the anti derivative= x^2 -.8x +C. Ignore C.
Plug in 2= 4-(2)(.8)=2.4
Plug in .4= .16-(.4)(.8)=-.16
2.4-(-.16)= 2.56
Answer:
5
Step-by-step explanation:
1) origin point is (0;0);
2) the required distance is:
![d=\sqrt{(-3-0)^2+(4-0)^2} =5.](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28-3-0%29%5E2%2B%284-0%29%5E2%7D%20%3D5.)
If you divide 180 by 12 you will get 15 and if you divide 180 by 15 you will get 12 then subtract both products and i t will give you the answer 3
Answer: (-9,6)
Step-by-step explanation:
3x+2y=-15
2x=-18
First solve for x in second equation
2x=-18
2x/2=-18/2
X= -9
Now substitute your x into first equation to find y
3(-9)+2y= -15
-27+2y=-15
2y= -15+27
2y= 12
2y/2=12/2
Y= 6